Study on the effects of plasticiser types and contents on physicochemical properties of HPMC/Shellac composite films - Thu Trang Pham; Thanh Tung Nguyen; Thi Thu Ha Pham; Trung Duc Nguyen; Van Khoi Nguyen; Quang Huy Nguyen; Cong Hoan Do; Vu Thang Tran; Thi Phuong Hoang; Phan Hang Nguyen (Vietnam Journal of Science, Technology and Engineering, 2022)
The objective of this work was to study the effects of different plasticisers [glycerol (G), propylene glycol (PG), polyethylene glycol 400 (PEG 400)] at different contents (10-30% compared to hydroxypropyl methylcellulose (HPMC)) on the properties of HPMC/shellac composite films. Sensory, mechanical properties, and surface morphology were used to evaluate changes in the composite films by adding different plasticisers. The results showed that with the addition of plasticisers, the films became more transparent and flexible. As the plasticiser content increased, the tensile strength and elastic modulus of the films decreased. At a plasticiser content of 20%, the water vapor permeability (WVP) of the composite films reached its minimum value. The SEM images showed that the HPMC/shellac composite film containing 20% G had the smoothest surface, and the components of this film were uniformly distributed.